The acceptance of ride-sharing mobile application (GrabCar) in Klang valley / Wan Jamilin Insyirah Wan Mohd Zaini - Wan Mohd Zaini, Wan Jamilin Insyirah (2019)
The presence of GrabCar as a smartphone-based taxi booking application in today’s modern world has been a game changer for mobility. However, the complaints and criticisms regarding the mobile application from its users regularly arise. There is the need to study the acceptance of The GrabCar mobile application in order to gain a better understanding about it as well as to provide solutions to the said matter. Accordingly, Technology Acceptance Model (TAM) theory was adopted to accomplish the study. A total of 400 questionnaires were distributed to people who reside in Klang Valley that includes Gombak, Petaling Jaya, Klang, Hulu Langat and Kuala Lumpur. The result revealed that there is a high acceptance of The GrabCar mobile application among Klang Valley community. It was also found that there is a significant relationship between Perceived Usefulness and Perceived Ease of Use with the Behavioral Intention. Next, Perceived Usefulness is the most contributing factor for the acceptance towards the GrabCar mobile application. It is also discovered that Age does not moderate the relationship between all variables in the conceptual framework for this study. Following to the findings, it is suggested that the related parties to initiate a quick and effective solution in addressing the matter. Meanwhile, future researchers are encouraged to improvise and expand the same context of study based on the recommendations given. Finally, it is hoped that the study is able to benefit to one and all.